2015
DOI: 10.1038/am.2015.28
|View full text |Cite
|
Sign up to set email alerts
|

POSS ionic liquid crystals

Abstract: Here we report the use of unique organic − inorganic hybrid materials composed of octa-substituted polyhedral oligomeric silsesquioxane (POSS) cores as ionic liquid (IL) crystals. These materials have a wide temperature range in which they exist in liquid crystal (LC) phase because of the stabilizing effect of the POSS core. We synthesized ion pairs composed of alkyl chainsubstituted imidazolium and carboxylates of various lengths that were or were not connected to the POSS core; then the thermal properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 30 publications
2
38
0
Order By: Relevance
“…In addition, it was shown that POSS can contribute to the extension of the temperature range as an ionic liquid crystal. 125 Thermodynamic studies revealed that the structural features of the POSS core such as symmetry and steric shape should be responsible for unique thermal properties of POSS ILs such as the lower melting temperatures and the higher thermal stabilities.…”
Section: ¹1mentioning
confidence: 99%
“…In addition, it was shown that POSS can contribute to the extension of the temperature range as an ionic liquid crystal. 125 Thermodynamic studies revealed that the structural features of the POSS core such as symmetry and steric shape should be responsible for unique thermal properties of POSS ILs such as the lower melting temperatures and the higher thermal stabilities.…”
Section: ¹1mentioning
confidence: 99%
“…Protonation and deprotonation of the nitrogen atom also make halochromism possible. Furthermore, many BF 2 bdks can be efficiently excited by both 1- and 2-photon absorption, to display bright, color tunable emission with quantum yields (ϕ) that approach unity, 24 and this research is improving upon their already desirable properties. Additional benefits of the azepane substituent include: 1) a large ε value contributes to high brightness (ε × ϕ), and 2) a strong amine donor can lead to red-shifted emission, expanding the set of achievable emission colors for multiplexing applications.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34] As a result, room-temperature ILs, which are defined as ionic salts with a melting temperature below 25°C, were produced based on POSS. Based on these characteristics of POSS ILs, we next sought to transmit the POSS effect on thermal properties to the IL matrices via non-covalent bonds ( Figure 5).…”
Section: Poss Element-blocks For Realizing Designable Hybridsmentioning
confidence: 99%